Multiple congenital anomalies and adverse developmental outcomes are associated with neonatal intensive care admission and unilateral hearing loss - Horrocks, Lucy M.; Kitterick, Pádraig T.; Jayasinghe, Dulip S.; Willis, Karen R.; Martin, Katherine R. M.; Dixit, Abhijit; Thornton, Sally K. (Frontiers in Pediatrics, 2023)
Abstract Aim: To determine congenital and developmental outcomes of children with Unilateral Hearing Loss (UHL) who were admitted to the Neonatal Intensive Care Unit (NICU). Method: Retrospective, single-site study that followed 25 children with permanent congenital UHL and a NICU admission to a NICU of Nottingham University Hospital. Birth and two-year developmental follow-up data were collected. They were compared to matched control group who had a NICU admission but no hearing loss (matched on gestational age, weight and sex). Results: The median birthweights, gestational ages and number of days spent on the NICU for the UHL population were 2510g, 36 weeks, and 12 days respectively. Most children (20/25; 80%) with UHL and a NICU admission were diagnosed with a congenital anomaly within the first two years of life. Only half (13/25) of these children were diagnosed with a congenital anomaly at discharge. Children with UHL and a NICU admission were more likely than the matched group (NICU admission only; p<.001) to have multiple congenital anomalies. We found a positive association between multiple congenital anomalies and developmental impairment for the NICU graduates with UHL (p=.019). This UHL-NICU group were also more likely than the matched NICU children to have developmental impairment (7/25 vs 0/25; p=.01), speech and language therapy (13/25 vs 1/25; p<.001), inner ear malformations (14/25 vs 0/25, p<.001) or craniofacial anomalies (12/25 vs 2/25; p=.004). Interpretation: Children with UHL and a NICU admission were at high risk of congenital anomalies and certain adverse developmental outcomes. Improved congenital anomaly screening is needed at birth for this population. Having multiple congenital anomalies suggests closer developmental monitoring is needed. This study contributes towards producing clinical screening and management guidelines to ensure consistent high-quality care for this unique population.